Pengaruh Inflasi, Kebijakan Moneter, dan Volatilitas Pasar terhadap Perubahan Suku Bunga Pada Bank Pemerintah - Dian Rimayanti; Prisca Trifena Puspita; Sinta Tri Hapsari; Rakeen Kresna Putra Rasmanjaya; Maria Yovita R. Pandin (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to examine the influence of inflation, monetary policy, and market volatility on interest rate changes in state-owned banks in Indonesia during the 2019–2024 period. A quantitative associative approach was applied using secondary data collected from official financial reports. The analysis involved multiple linear regression, t-tests, and F-tests. The t-test results revealed that only inflation had a significant and negative impact on interest rates, while monetary policy and market volatility did not show significant effects. Simultaneously, the F-test indicated that the three variables did not significantly influence interest rates, supported by a low Adjusted R² value of only 13.4%. These findings suggest that other external factors outside the model play a more dominant role in determining interest rate fluctuations. The results emphasize the critical importance of inflation control and the need for a more comprehensive approach in shaping interest rate policy within state-owned banking institutions.